Der sogenannte Hadrianstempel an der Kuretenstraße, Tafelband - Quatember, Ursula (Verlag der Österreichischen Akademie der Wissenschaften, 2018)
The publication on the so-called "Temple of Hadrian" on Curetes' Street in Ephesos is the first comprehensive publication of this important monument from the Roman Imperial period in Asia Minor. Based on new research on architecture, inscriptions, and decoration, a contextual interpretation allows us to understand the temple in the context of the cult for the city goddess Artemis and ritual processions through the Ephesian city center in her honor.Text see: http://e-book.fwf.ac.at/o:1150Maps see: http://e-book.fwf.ac.at/o:1152